European Perspectives:: New proposal for sustainable urban transport plans across Europe - Stead, Dominic (European Journal of Transport and Infrastructure Research, 2004)
Urban transport systems are critical elements of the urban fabric. They ensure that people have access to goods, services, employment and recreation opportunities, that freight circulates efficiently and they enable local economies to flourish. However, if the high density of buildings is the first defining characteristic of towns and cities, then high volumes of traffic is now the second. Traffic has significant impacts on the environment and on the health of urban citizens, as well as on the overall quality of life in towns. Rising congestion levels are hampering mobility, with increasing costs for the economy (0.5% of Community GDP for road traffic congestion, rising to 1% by 2010).